ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP FINANCIAL DISTRESS DENGAN FINANCIAL PERFOMANCE SEBAGAI VARIABEL MODERASI (Studi Empiris Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Dewi, Putri Ayu Nuraini; Rosyadi, Imron (JURNAL ILMIAH EDUNOMIKA, 2024)
This research investigates the impact of Good Corporate Governance (GCG) practices on Financial Distress, with Financial Performance serving as a moderating factor. The study focuses on manufacturing enterprises within the food and beverage sub-sector during the period of 2020 to 2022. Employing a quantitative approach, the researchers gathered secondary data from the Indonesia Stock Exchange (IDX). The sample selection process utilized purposive sampling techniques, resulting in a final sample of 12 companies, yielding a total of 36 data points for analysis. To examine the relationships between variables, the researchers employed Panel Data Regression analysis and Moderated Regression Analysis (MRA). The findings reveal that Good Corporate Governance does not exert a significant influence on financial distress. However, when considering leverage as a moderating variable, it demonstrates the ability to moderate the relationships between institutional ownership, board of directors' composition, and board of commissioners' structure in relation to financial distress. Interestingly, leverage fails to moderate the associations between managerial ownership and audit committee characteristics with financial distress. Keywords: Good Coorporate Governance, Financial Distress, Financial Perfomance, Leverage